Analisa Penambahan Jam Lembur Kerja dengan Metode Crash Program pada Proyek Pembangunan Terminal Tipe B Gorontalo - Tandimas Febriyanto; Moh Yusuf Tuloli; Arfan Utiarahman (Transbahasa, 2025)
Delays in project execution can be addressed through project control techniques such as the crash method, which aims to accelerate project duration without significantly increasing costs. This study investigates the application of the crash method in the acceleration of a Type B Terminal construction project (Phase 1) to evaluate its impact on project duration and cost. The research employs a quantitative descriptive approach, combining literature review and field observation. Data collection includes the original project schedule and cost information, followed by critical path analysis using the Critical Path Method (CPM). Based on the identified critical activities, the study applies crash analysis by reducing the duration of critical tasks and adding overtime hours, then compares various scenarios to determine the most cost-effective acceleration strategy. The results reveal that an additional 4 hours of overtime is the most efficient option, reducing the project duration by 43% while incurring the lowest total cost of Rp 3,860,600,576.59. This finding highlights that proper application of the crash method can lead to substantial time savings with manageable cost implications. In conclusion, the crash method proves to be an effective strategy for project time optimization when supported by accurate scheduling, cost analysis, and critical activity identification. The study recommends further research to validate these findings across different types of infrastructure projects using updated specifications.